A Social Network Approach to Social Media Influencers on Instagram: The Strength of Being a Nano-Influencer in Cause Communities. Issue 1 (2nd January 2023) - Himelboim, Itai; Golan, Guy J.
Abstract: Emerging literature on social media influencers (SMIs) identifies their potential to help brands gain attention and build credibility with consumers, in particular as brands respond to the growing consumer expectation of a commitment to social causes. We propose a social networks approach to the study of paid SMIs and implement it in veganism cause-related communities on Instagram. Findings identify clusters, echo chambers of influencers promoting similar products, associated with different facets of the cause community. Findings illustrate the value of a different type of SMI who bridges across influencers' clusters and their following consumers. The study reveals the power of nano-influencers, who exhibited higher betweenness centrality levels, that is, their bridging position in the network. Conceptually, this study connects network scholarship to the study of paid influencers. We discuss methodological and practical implications of the potential role of influencers in brand attempts to engage with online cause communities.